Identification of the Identity of Remote Area Teacher as a Driving Force - Elisabeth Desiana Mayasari (Universitas Pendidikan Ganesha, 2022)
Being a teacher is important and impactful for the society. The identity of the teacher reflects personal characteristics that contribute to the success of the learning process. Remote Area Teacher as a Driving Force (ATDF) is a program to advance Mappi Regency in the field of education. In the process of mentoring students, ATDF teachers need to know the identities they have. The purpose of this study was to determine the identity of the Remote Area Teachers as a Driving Force based on the types of teacher legitimization. The populations in this study were the Remote Area Teachers. The method used in this research was descriptive quantitative. The instruments used were questionnaires and interviews based on teacher legitimization, which were conducted on two ATDFs. The researcher used the data analysis model including: 1) Data Collection, 2) Data Reduction, 3) Data Display (Data Presentation), and 4) Conclusion Drawing / Verification. The results show that the ATDF teachers own the following types of identity: 1) Caring legitimization type, 2) Contextual legitimization type and 3) Psychological legitimization type. Those identities show that ATDF teacher 1) have a caring attitude towards student interests, 2) pay attention to students’ life which is reflected in the learning process in class and 3) focus on students' interests and behavior psychologically.